The relationship between authoritarian parenting style, emotional intelligence and cyber aggression in university students - Agata Ika Paskarista; Suparmi -; Emiliana Primastuti (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This study aims to investigate the relationship between authoritarian parenting style, emotional intelligence, and cyber aggression in undergraduate students in a private university in Central Java. There were three hypotheses tested in the study, including 1) the major hypothesis: there is a relationship between authoritarian parenting style, emotional intelligence and cyber aggression; 2) the first minor hypothesis: there is a positive relationship between authoritarian parenting style and cyber aggression; and 3) the second minor hypothesis: there is a negative relationship between authoritarian parenting style and cyber aggression. This was a quantitative correlational study conducted on 105 research subjects. The data were collected using the authoritarian parenting style scale, the emotional intelligence scale and the cyber aggression scale. The results of hypothesis testing showed that there is a relationship between authoritarian parenting style, emotional intelligence and cyber aggression (R=0.476; p<0.01). The results of the first minor hypothesis testing found a positive relationship between authoritarian parenting style and cyber aggression (rxy=0.386; p<0.05). The results of the second minor hypothesis testing found a negative relationship between emotional intelligence and cyber aggression (rxy=-0.402; p<0.05). The statistical test results showed that the three hypotheses were accepted. This study is hoped to encourage university administrators to consider the procurement of a program aiming to reduce students’ cyber-aggression behavior.